2018
DOI: 10.1111/gcb.14147
|View full text |Cite
|
Sign up to set email alerts
|

Global effects of plant litter alterations on soil CO2 to the atmosphere

Abstract: Soil respiration (Rs) is the largest terrestrial carbon (C) efflux to the atmosphere and is predicted to increase drastically through global warming. However, the responses of Rs to global warming are complicated by the fact that terrestrial plant growth and the subsequent input of plant litter to soil are also altered by ongoing climate change and human activities. Despite a number of experiments established in various ecosystems around the world, it remains a challenge to predict the magnitude and direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 78 publications
(145 reference statements)
3
40
1
Order By: Relevance
“…Plants play a decisive role in regulating Rs since they are the principal pathways through which carbon enters the soil (Chen & Chen, ). Biomass production increases with plant species diversity and trait heterogeneity due to complementary resource utilization among constituent species in species‐rich ecosystems (Hooper et al, ; Zhang, Chen, & Reich, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants play a decisive role in regulating Rs since they are the principal pathways through which carbon enters the soil (Chen & Chen, ). Biomass production increases with plant species diversity and trait heterogeneity due to complementary resource utilization among constituent species in species‐rich ecosystems (Hooper et al, ; Zhang, Chen, & Reich, ).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass production increases with plant species diversity and trait heterogeneity due to complementary resource utilization among constituent species in species‐rich ecosystems (Hooper et al, ; Zhang, Chen, & Reich, ). The higher biomass production in species‐rich ecosystems is expected to increase Rs primarily by increasing respiration in living roots and their associated rhizomicrobial and microbial communities (Chen & Chen, ; Kuzyakov & Gavrichkova, ). Higher plant diversity can also increase soil microbial respiration because of a higher quantity and multiplicity of plant‐derived food resources that enter the soil as well as expanded niches for microbes associated with a higher microenvironment variability and habitat complexity (Chapman & Newman, ; Eisenhauer et al, ; Hector, Beale, Minns, Otway, & Lawton, ; Hooper et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 100 published experimental studies found that a 100% aboveground litter addition (i.e. double litter) increased heterotrophic respiration by 26.1% (Chen and Chen 2018). Additionally, increased inputs of fresh organic matter resulting from litterfall could result in 'priming effects'.…”
Section: Discussionmentioning
confidence: 99%
“…Litterfall is a particularly key process for determining the carbon and nutrient cycling of terrestrial ecosystems, and it controls the main respiration substrates on the forest floor (Roig et al 2005, Chen andChen 2018). The magnitude of litterfall regulates the rate of soil respiration and soil organic carbon content indirectly (Sayer 2006, Hansen et al 2009, Neumann et al 2018.…”
Section: Introductionmentioning
confidence: 99%